Analysis of Continuance Use Intention in Mobile Banking Using the Extended Expectation Confirmation Model - Eva Khudzaeva; Rinda Hesti Kusumaningtyas; Uden Agustian Hidayat; Eri Rustamadji; Chandra Wirawan (Jurnal Informasi dan Teknologi, 2025)
Continuation intention refers to the user's desire to continue using a service or application in the long term after their initial experience. In the context of mobile banking applications, continuance intention is very important to maintain and increase the number of active users, as well as maintain customer loyalty. Although mobile banking can facilitate financial transactions, there are still complaints from users with many negative reviews on the Play Store and App Store regarding the problematic OTP verification and delivery process. This study aims to identify variables that influence the continuance intention to use mobile banking. This study uses the ECM research method to examine the factors that influence the intention to continue using mobile banking. This study tested nine hypotheses, with the results of seven hypotheses accepted and two hypotheses rejected, namely the relationship between trust → satisfaction with a t-test result of 0.755 and confirmation → satisfaction with a t-test result of 0.351. It is expected that the results of this study can provide recommendations to mobile banking parties to improve services and increase user satisfaction, thereby maintaining the loyalty of mobile banking users. In addition, this study can be a reference for quantitative research in the field of mobile banking and contribute to the development of strategies and policies to improve user experience.